Constructing Adaptation Pads in A Form of MSME Resiliency Strategies in PT Nusantara Totalindo Logistics - Rizky Anugrah Pratama, Muhammad; Shalihati, Fithriyyah; Herlina, Lien (School of Business, IPB University (SB-IPB), 2023)
PT Nusantara Totalindo Logistics (PT NTL) is a company engaged in the logistics transportation sector with fast business growth but is currently in the business introduction and business turbulence phase. In facing the business introduction phase and business turbulence, it is necessary to develop business resilience and adaptation strategies. This study aims to identify PT NTL's business potential and advantages, build business resilience for PT NTL by establishing PT NTL's vision and mission as a corporate statement to support the completeness of organizational documents and designing business resilience formulations for PT NTL through creating work programs, organizational structure, business model canvas, business processes, and business risk mitigation to build a business adaptation strategy. The data for this research were sourced from in-depth interviews and risk management research questionnaires. Based on the results of the study that has been done, a time-framed business adaptation-bearing formulation has been formed through six processes, starting from vision and mission formation to risk management that has adaptation and resilience properties. Business in the face of business turbulence. The management implications of a business resilience strategy are the establishment of a vision and mission according to the resilience and business adaptation strategy, a comprehensive organizational structure, work programs for the next five years according to business turbulence and disruption, a kanas business model that supports work programs up to logistics risk management. Keywords: business introduction phase, risk management, business risk, transportation collaboration system, business turbulence